Solar cycle variation of νmax in helioseismic data and its implications for asteroseismology. (8th January 2020) - Howe, Rachel; Chaplin, William J; Basu, Sarbani; Ball, Warrick H; Davies, Guy R; Elsworth, Yvonne; Hale, Steven J; Miglio, Andrea; Nielsen, Martin Bo; Viani, Lucas S
ABSTRACT: The frequency, νmax, at which the envelope of pulsation power peaks for solar-like oscillators is an important quantity in asteroseismology. We measure νmax for the Sun using 25 yr of Sun-as-a-star Doppler velocity observations with the Birmingham Solar-Oscillations Network (BiSON), by fitting a simple model to binned power spectra of the data. We also apply the fit to Sun-as-a-star Doppler velocity data from Global Oscillation Network Group and Global Oscillations at Low Frequency, and photometry data from VIRGO/SPM on the ESA/NASA SOHO spacecraft. We discover a weak but nevertheless significant positive correlation of the solar νmax with solar activity. The uncovered shift between low and high activity, of $\simeq 25\, \rm μ Hz$, translates to an uncertainty of 0.8 per cent in radius and 2.4 per cent in mass, based on direct use of asteroseismic scaling relations calibrated to the Sun. The mean νmax in the different data sets is also clearly offset in frequency. Our results flag the need for caution when using νmax in asteroseismology.